1993
DOI: 10.1128/jcm.31.8.2241-2243.1993
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of African horse sickness virus in The Gambia

Abstract: An indirect enzyme-linked immunosorbent assay was used for the screening of horse sera from The Gambia for antibodies against African horse sickness virus (AHSV). The AHSV antigen used for coating was semipurified according to the method of Manning and Chen (Curr. Microbiol. 4:381, 1980); control mock-infected Vero cell antigen was treated in the same manner. A total of 459 horse serum samples were assayed at a single dilution (1:10), and their reactivities were compared with those of reference positive anti-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Contrary wise, many studies have reported the prevalence of antibodies with results comparable to that obtained in this work. Indeed, seroprevalence was higher than that obtained in Ethiopia (46%) [ 24 ], but lower than 86.6% reported in Nigeria [ 22 ], 91.81% in Senegal [ 12 ], and 81% in Gambia [ 23 ]. The difference may be related to the variation in agroecological contexts and the control strategy develops in each country.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Contrary wise, many studies have reported the prevalence of antibodies with results comparable to that obtained in this work. Indeed, seroprevalence was higher than that obtained in Ethiopia (46%) [ 24 ], but lower than 86.6% reported in Nigeria [ 22 ], 91.81% in Senegal [ 12 ], and 81% in Gambia [ 23 ]. The difference may be related to the variation in agroecological contexts and the control strategy develops in each country.…”
Section: Discussionmentioning
confidence: 63%
“…The climatic conditions in sub-Saharan Africa facilitates the permanent survival of vectors throughout the year [ 21 ] and the use of live vaccines in nonenzootic areas (risk of reversion to virulent strains) [ 16 ]. AHS is endemic in sub-Saharan Africa, and the estimated prevalence of antibodies in horses of 86.6% [ 22 ], 81.% [ 23 ], and 46.% [ 24 ] was reported in Nigeria, Gambia, and Ethiopia, respectively. In Cameroon, there is little or no information regarding the profile of AHS.…”
Section: Introductionmentioning
confidence: 99%
“…Declining rainfall in the last three decades, a reduction of suitable tsetse habitat (Rawlings et al, 1993) and tsetse challenge (Rawlings et al, 1991;Snow et al, 1996), has been matched by an increasing number of equines in most districts of The Gambia to about 18 000 horses and 34 000 donkeys (Rawlings et al, 1992;Sumberg & Gilbert, 1992;NADC, 1995). Recent studies on the serology of AHSV have shown that more than 90% of horses and all donkeys tested were seropositive up-river in The Gambia (Mattioli et al, 1992;Stäuber et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study conducted in The Gambia by Staeuber et al . [10], 81% of the 459 horse serum samples collected tested seropositive for AHSV antibodies. The high percentage of AHSV antibody-positive horses in The Gambia along with a lack of clinical signs suggest that either the local breeds of horses may be resistant to AHS or alternatively the AHSVs circulating may not be virulent.…”
mentioning
confidence: 99%